From screens to carts: the role of emotional advertising appeals in shaping consumer intention to repurchase in the era of online shopping in post-pandemic - Alshohaib, Khalid Ali (Frontiers in Communication, 2024)
This study examines the evolving dynamics of online shopping behavior in the post-COVID-19 era, focusing on the intricate relationship between perceived usefulness, ease of use, pleasure, arousal, dominance emotional state, and intention to repurchase by integrating and employing the technology acceptance model and pleasure, arousal, and dominance emotional model. These emotional states, identified as pivotal drivers of online shopping behavior, contribute to recognizing a brand's function and aesthetic features. 509 male and female respondents from Saudi Arabia participated in the present study. The statistical tools unveil significant indirect relationships and mediation effects, offering insights into the nuanced pathways through which perceived usefulness and ease of use impact consumer intentions to repurchase. Demographic variables, particularly age, and gender, are explored to understand variations in emotional responses, guiding businesses in tailoring marketing strategies to diverse consumer segments. Practical implications highlight the importance of strategic considerations for brand retailers, emphasizing enhancements to elements related to emotional branding, product presentations, interface design, and interactive services on websites. The research advocates for a dynamic and personalized approach to online experiences, positioning brands favorably in the competitive digital landscape. Overall, the findings contribute valuable insights for businesses seeking to navigate the dynamic terrain of post-COVID-19 online shopping and foster enduring connections with their digital consumer base.